From Salt to Votes: Civic Resistance, Regime Collapse, and Cartel Politics in Malaka, Indonesia - Rohi, Rudi; Pradana, I Putu Yoga Bumi; Benu, Esrah D. N. A.; Humau, Frans; Lopo, Yonatan; Rijoly, Jacobus Cliff Diky (Journal Public Policy, 2025)
This study aims to examine how the governance of the salt industry in Malaka Regency, East Nusa Tenggara, Indonesia, affects local democracy, particularly by distinguishing between procedural and substantive democratic outcomes. Despite growing interest in the democratic implications of natural resource governance, existing studies on coastal extractive resources often conflate these two dimensions, leading to mixed conclusions. Employing a qualitative single-case study approach, data were collected through field observations, in-depth interviews, focus group discussions, and desk research. The findings reveal that salt governance in Malaka triggered grassroots resistance and significantly increased voter turnout in the 2020 regional elections, ultimately contributing to the fall of a dominant political dynasty. These developments reflect a strengthening of procedural democracy through heightened civic engagement and electoral accountability. However, the same governance processes resulted in substantive democratic failures, including land dispossession, environmental degradation, and violations of customary rights. Furthermore, the political transition led to the rise of a cartel-style regime, where elites reconfigured power through alliances among business actors, bureaucrats, and political leaders. This study concludes that coastal extractive governance can simultaneously advance procedural democracy while undermining substantive democracy and calls for a more nuanced evaluation of democratic quality in resource-dependent, decentralized regions.